Lingkup Teori Organisasi Pada Pelayanan Kesehatan - Widjaja, Yani Restiani; Purwadhi, Purwadhi; Maharani, Dessy; Setiati Putri, Paramita Indah (Jurnal sosial dan sains, 2025)
Healthcare services are a vital component of social development, demanding effective, efficient, and adaptive organizational governance in response to changing environments. This study aims to analyze the contribution of organizational theories in enhancing the performance of healthcare service organizations, focusing on four key approaches: bureaucracy theory, open systems theory, contingency theory, and transformational leadership theory. This research employs a Systematic Literature Review (SLR) method with a qualitative approach, conducted in a systematic, transparent, and replicable manner. Ten scholarly articles published between 2019 and 2024 were analyzed thematically to explore the relationships among theories, patterns of implementation, and their impact on the effectiveness of hospitals and community health centers (puskesmas). The results indicate that bureaucratic theory remains foundational in the structural arrangement of public hospitals, but must be complemented by flexibility to avoid hindering innovation. Open systems theory emphasizes the importance of integration across organizational units and responsiveness to external influences. Meanwhile, contingency theory highlights the necessity of aligning organizational structures and strategies with local contexts and resource capacities. Transformational leadership plays a crucial role in driving positive change, increasing staff participation, and fostering service innovation. This study concludes that integrating all four organizational approaches is essential to shaping a healthcare management model that is adaptive, collaborative, and oriented toward quality and sustainability. The findings serve as both conceptual and practical references for healthcare facility managers, policymakers, and scholars in the field of health management.